Condition assessment of power transformer onload tap changers using wavelet analysis and self-organizing map field evaluation. - Pengju Kang
An onload tap changer (OLTC) is the most maintenance intensive subassembly on a power transformer. Vibration monitoring is an effective technique that can be used to assess the condition of an OLTC nonintrusively. The authors have developed a condition monitoring system for common types of OLTCs that enables the condition of tap changer contacts and associated drive system to be inferred from vibration signals. A number of prototype systems have been installed onto OLTCs in distribution zone substations for field trials. Particular emphasis has been given to the detection of faults in a particular type of older tap changer that had been prone to a range of faults associated with the switching contacts and drive mechanism. For this type of tap changer, it has been shown to be possible to determine not only that the tap changer is aging but also to identify the particular part that is degrading.
Keywords: Condition assessment; Distribution zone substations; Drive mechanism; Drive system; Fault detection; Faults detection; Power transformer onload tap changers; Self-organizing map; Switching contacts; Tap changer contacts; Vibration monitoring; Vibration signals; Wavelet analysis; Wavelet transform